2003
DOI: 10.1209/epl/i2003-00261-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the dendritic flux instability in YBa 2 Cu 3 O 7 − δ films

Abstract: Abstract. -We have studied the dynamics of magnetic-flux avalanches in superconducting YBa2Cu3O 7−δ films by means of a fast magneto-optic pump-probe technique. Two regimes of propagation are found: in regime I, directly after the nucleation of the avalanches by a femtosecond laser pulse, the velocity v of the flux dendrites depends strongly on the magnetic field, and values of v up to 180 km/s are observed. Within some ten nanoseconds after nucleation regime II is reached, where the propagation velocity has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 16 publications
5
81
0
Order By: Relevance
“…2(c), where individual branches are resolved, we find an average speed of 5 km/s, using a branch length of 0.15 mm formed during a time interval (equal to the pulse halfwidth) of 30 ns. This speed is 3-4 times less than that reported by Bolz et al 9 for the late stage of dendritic avalanches in YBa 2 Cu 3 O x . At 10 K, they found a speed, which in the very early stages of an avalanche has values near 150 km/s, and then decreasing to 18 km/s at the later stages.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…2(c), where individual branches are resolved, we find an average speed of 5 km/s, using a branch length of 0.15 mm formed during a time interval (equal to the pulse halfwidth) of 30 ns. This speed is 3-4 times less than that reported by Bolz et al 9 for the late stage of dendritic avalanches in YBa 2 Cu 3 O x . At 10 K, they found a speed, which in the very early stages of an avalanche has values near 150 km/s, and then decreasing to 18 km/s at the later stages.…”
mentioning
confidence: 51%
“…Previous work on films of YBa 2 Cu 3 O x has combined MOI and a femtosecond pulsed laser technique, where an avalanche was triggered by a laser-generated hot spot, and a few nanoseconds later laser light was used to record a snapshot of the evolving flux distribution. 9 From such measurements, it was found that at the initial stage the flux branches grow at speeds near a hundred kilometers per second. Using that method, however, little information was obtained about the dynamic electrical field generated during avalanche events.…”
mentioning
confidence: 99%
“…Once triggered, avalanches in superconducting films advance at very high speeds, typically ranging from units to several tens of km/s [1,33,34], usually faster at the early stages. Such events are thus so fast that no instrumentation is currently available to capture a substantial set of images of such events while they occur.…”
Section: Modelingmentioning
confidence: 99%
“…Such interface rushes deeper into the sample in an attempt to establish the lowest energy state, for which flux distribution should be smooth throughout the system. The supersonic propagation of these fronts can exceed by several orders of magnitude the typical speed of individual flux quanta [1]. For this reason, one cannot expect to draw meaningful predictions about evolution and shape of avalanches by simply extrapolating the dynamics of individual quantized superconducting vortices.…”
Section: Introductionmentioning
confidence: 99%
“…3 Magnetooptical imaging (MOI) experiments have shown that the flux dendrites can grow during the runaway to lengths on the order of the sample size in approximately 100 ns. 4 When triggered by an increasing external magnetic field, the avalanches nucleate and start propagating from the film edge where the exact starting point is essentially unpredictable, since disorder like edge roughness plays a key role. Due to disorder also within the film, the detailed propagation route of an avalanche is unpredictable too.…”
mentioning
confidence: 99%